2019
DOI: 10.1111/gcb.14860
|View full text |Cite
|
Sign up to set email alerts
|

Soil fauna diversity increases CO2 but suppresses N2O emissions from soil

Abstract: Soil faunal activity can be a major control of greenhouse gas (GHG) emissions from soil. Effects of single faunal species, genera or families have been investigated, but it is unknown how soil fauna diversity may influence emissions of both carbon dioxide (CO2, end product of decomposition of organic matter) and nitrous oxide (N2O, an intermediate product of N transformation processes, in particular denitrification). Here, we studied how CO2 and N2O emissions are affected by species and species mixtures of up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 74 publications
3
9
0
1
Order By: Relevance
“…Hamidov et al (2018) Lavelle et al (2014) (continued on next page) Hagvar (1998) & ''soil biodiversity''. However, with the removal of the word 'threat' from the search references are being returned that not only report the impacts of climate change on soil biodiversity, but also the ecosystem services provided by soil biodiversity in terms of climate change mitigation (e.g., Lubbers et al, 2019). From this broader bibliographic analysis, we concluded that threats to soil biodiversity was the appropriate focus of this review, and the use of the search term threat* ''soil biodiversity'' was therefore rational in this instance.…”
Section: Identifying Drivers and Threats To Soil Biodiversitymentioning
confidence: 99%
“…Hamidov et al (2018) Lavelle et al (2014) (continued on next page) Hagvar (1998) & ''soil biodiversity''. However, with the removal of the word 'threat' from the search references are being returned that not only report the impacts of climate change on soil biodiversity, but also the ecosystem services provided by soil biodiversity in terms of climate change mitigation (e.g., Lubbers et al, 2019). From this broader bibliographic analysis, we concluded that threats to soil biodiversity was the appropriate focus of this review, and the use of the search term threat* ''soil biodiversity'' was therefore rational in this instance.…”
Section: Identifying Drivers and Threats To Soil Biodiversitymentioning
confidence: 99%
“…However, after this initial increase, the damage in the canopy may lead to the opposite effect, and may open the soil to drying and to large diurnal variations in soil CO 2 respiration (Vargas & Allen, 2008a); this is a major driver of the nitrogen cycling and belowground carbon dynamics (Hasselquist, Santiago, & Allen, 2010). Regardless of mechanisms, short‐term fluctuations in soil CO 2 concentrations (and other greenhouse gases) lead to variability in soil emissions (Barcellos et al., 2018; Fernandez‐Bou, Dierick, & Harmon, 2020; Fernandez‐Bou et al, 2018; Harms & Grimm, 2008; Haverd, Ahlström, Smith, & Canadell, 2017; Kuzyakov & Blagodatskaya, 2015; Leon et al., 2014; Lubbers, Berg, Deyn, van der Putten, & van Groenigen, 2019; Soper et al., 2019; Swanson et al., 2019; Vargas et al., 2018). In this work, we monitor soil CO 2 concentration over multiple years to better understand its short‐term dynamics and potential influence on tropical soil CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Their role in soil organic matter (SOM) dynamics, though, is often neglected despite their presence in many ecosystems worldwide (Hendrix et al, 2008). Earthworms affect SOM dynamics in two principal ways: (1) they stimulate soil microbial activity and biomass and, thus, enhance the mineralization of SOM (i.e., the release of CO 2 into the atmosphere; Ferlian et al, 2018;Groffman et al, 2015;Lubbers et al, 2019;McLean et al, 2006) and (2) they promote the formation of macro-and microaggregates, transferring SOM into a more stabilized form (Bossuyt et al, 2005;Pulleman et al, 2005). The net effect of these processes on the storage of soil organic C (SOC), though, is still subject to debate likely due to a focus on coarse-scale measures, such as the SOC contents of bulk soil.…”
mentioning
confidence: 99%